“I AM has sent me to you:” How Thomas Aquinas’ understanding of the divine names illuminates the way in which he reconciles impassibility and compassion in God - Reynolds, Susan Bigelow (Lumen et Vita, 2013)
Contemporary debates on divine impassibility generally offer two options: either affirm a suffering God who loves and cares, or uphold an impassible God who turns a blind eye to the cries of his people. For Thomas Aquinas, divine impassibility (along with the other divine attributes: simplicity, infinity, immutability, etc.) is not inconsonant with divine compassion. God’s unchangeable nature affirms, not undermines, God’s ability to love. This paper, acknowledging the inadequacy of these two incomplete and dichotomous categorizations, will argue that Thomas’ understanding of the divine names in the Summa Theologiae, 1a, q. 13 illuminates the way in which he reconciles impassibility and compassion in God. It is not the goal of this paper to defend either the idea that God does or does not suffer, nor to affirm or deny the doctrine of divine impassibility on a scale any larger than the work of Thomas and selected contemporary scholars who assist in the project of unpacking and analyzing his thought. It is the goal of this paper to examine in as close a way as possible how Thomas’ defense of divine impassibility can be placed in dialogue with his understanding of the way that humans know and name God, ultimately revealing the inadequacy in the polarizing assumption that an immutable God cannot love. I will begin by analyzing the structure and implications of Thomas’ defense of divine impassibility in Question 9. This will be followed by an analysis of how, in Thomas’ understanding, human knowledge of God, including God’s attribute of impassibility, affects human capacity to name God, here drawing heavily on the insights David Burrell. I will then explore the theological and scriptural implications of Thomas’ assertion that “The One Who Is” is the most appropriate name for God, ultimately arguing that an understanding of the Hebrew scripture from which this name is drawn reveals that God’s love and compassion on behalf of his suffering people is not opposed to but rather relies upon his unchanging nature.